Studi Pengaruh Pelayanan dan Harga terhadap Pembelian ShopeeFood di SMA Unggulan Amanatul Ummah: Studi di SMA Unggulan Amanatul Ummah - Hidayat, Herman; Augustinah, Fedianty; Listyawati, Liling (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2024)
This study aims to examine the effect of service quality and price on purchase decisions in the ShopeeFood service, both partially and simultaneously. This research uses a survey method involving 100 students from SMA Unggulan Amanatul Ummah Surabaya as respondents. The data analysis technique used is multiple linear regression analysis. This technique utilizes incidental sampling, and the data is further analyzed using instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results show that partially, service quality has a significant negative effect on purchase decisions, while price has a significant positive effect. Simultaneously, these two variables significantly affect purchase decisions, with an Adjusted R Square value of 0.846, meaning 84.6% of the variation in purchase decisions can be explained by service quality and price. Based on these results, it is recommended that ShopeeFood continues to improve its service quality and establish competitive pricing strategies to attract more consumers.